Investigating the Role of Islam in Shaping Political Identity in Gorontalo - Mukrimin Mukrimin (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
This article examines how Islam has played a part in developing political identity in the Indonesian city of Gorontalo. It assess how Islam has changed over time in Gorontalo, how locals have interpreted it, and how contemporary perspectives on Islam's place in Gorontalo compare to those of the past. The lasting effects of Islam's sway over Gorontalo politics will then be evaluated. Islam has been practiced in Gorontalo for generations. Many historical narratives detail the first contacts between native peoples and Muslim settlers from Arabia, Yemen, and China, eventually leading to Islam's widespread embrace. Many in Gorontalo believed adopting Islam would help unify the area's disparate cultural groups and improve its political and social institutions. As a result, Shi'ite and Sunni communities developed in Gorontalo, and Islamic law and education were instituted there. Since the city of Gorontalo's founding, religion and politics have been inextricably entwined. Islamic political parties and movements have had a significant role in establishing the current government order in the area. Political authorities in the region frequently draw on Islamic ideas in making decisions, and the region's legal codes are in place to ensure social justice and political stability. Thanks to this, Islam's political legacy may be carried on from generation to generation.